PERTUMBUHAN INKLUSIF : FENOMENA PERTUMBUHAN INKLUSIF DI KAWASAN INDONESIA BAGIAN BARAT DAN INDONESIA BAGIAN TIMUR - Sholihah Amalina Dyah Hapsari; Manuntun Parulian Hutagaol; Alla Asmara (JURNAL EKONOMI DAN KEBIJAKAN PEMBANGUNAN, 2013)
The growth of the middle class in Indonesia that occurred during the last ten years allegedly raised by the economic growth that is likely to increase in the same period. An economic theory which states that inclusive growth is growth that is able to bring the middle class makes economists focus on inclusive growth and the middle class itself. But in fact, the middle class in Indonesia is dominated by the lower middle class whose features are similar to the poor. These issues indicate a gap in the economy. In addition, to talk about the gap, there is no doubt that this issue has long been a discussion in Indonesia, especially the gap between western Indonesia and eastern Indonesia. Therefore this study was conducted to analyze whether it is true that inclusive growth has occurred in Indonesia and how the phenomena that occur in the western part of Indonesia and eastern Indonesia. Based on the data from 33 provinces in Indonesia over a period of 5 years, ie from 2008 to 2012, this study of the Measured inclusive growth by adopting the concept formulated by Klasen (2010) on-Poverty Equivalent Growth Rate (PEGR). This study of the processing of data performed using Excel and SPSS software. The results found that economic growth in Indonesia in 20082012 has not been inclusive in reducing poverty, lowering inequality and increase employment. The results also show that inclusive growth is not a consistent phenomenon in Indonesia. The phenomenon of inclusive growth in reducing poverty, lowering inequality, and increasing employment are more prevalent in Western Indonesia (IBB).  Key words : inclusive, growth, middle class, panel data, excel